Penerapan selective policy oleh kantor imigrasi kelas I TPI Denpasar - Angelica Maharani Putri; Nugraha, A.A. Bagus Surya Widya (Institute for Advanced Science Social, and Sustainable Future, 2024)
The TPI Denpasar Class I Immigration Office is under the Directorate General of Immigration of the Ministry of Law and Human Rights. The TPI Denpasar Class I Immigration Office applies selection laws to ensure the integrity of prospective Indonesian Migrant Workers (PMI) who have non-procedural status when applying for a passport. This office is responsible for immigration functions, from issuing passports to law enforcement against foreign citizens (WNA) and Indonesian citizens (WNI). The purpose of this selective policy is to ensure that every PMI candidate who plans to work abroad meets all applicable requirements and conditions and is not involved in any legal violations that could endanger them in their intended workplace. This research was conducted qualitatively, using a descriptive approach. The research results show that the TPI Denpasar Class I Immigration Office has carried out immigration supervision in accordance with the law and legal provisions to prevent non-procedural PMI. Supervisory measures involve refusing to issue passports to PMI candidates suspected of working non-procedurally. In carrying out supervision in the field, immigration officers still face obstacles such as passport applicants providing incorrect information, manipulating data, and falsifying letters of recommendation for work.